2020
DOI: 10.3390/polym12092037
|View full text |Cite
|
Sign up to set email alerts
|

Caranan Fiber from Mauritiella armata Palm Tree as Novel Reinforcement for Epoxy Composites

Abstract: A growing environmental concern is increasing the search for new sustainable materials. In this scenario, natural lignocellulosic fibers (NLFs) became an important alternative to replace synthetic fibers commonly used as composites reinforcement. In this regard, unknown NLFs such as the caranan fiber (Mauritiella armata) found in South American rain forests revealed promising properties for engineering applications. Thus, for the first time, the present work conducted a technical characterization of caranan fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…However, these temperatures for all samples are slightly lower when compared to neat epoxy. These results corroborate previous studies in which natural fibers were used as epoxy matrix reinforcement [ 65 , 66 ]. Based on these results, a thermal stability limit of 296.3 °C can be established for untreated 40 vol% TVF composites and 268.8 °C for Na 2 CO 3 -treated 40 vol% TVF composites.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, these temperatures for all samples are slightly lower when compared to neat epoxy. These results corroborate previous studies in which natural fibers were used as epoxy matrix reinforcement [ 65 , 66 ]. Based on these results, a thermal stability limit of 296.3 °C can be established for untreated 40 vol% TVF composites and 268.8 °C for Na 2 CO 3 -treated 40 vol% TVF composites.…”
Section: Resultssupporting
confidence: 92%
“…The DSC curve for untreated and treated TVF, shown in Figure 7 b, initially presents endothermic peaks between 70–80 °C that refer to moisture loss and TVF T g . The T g found for TVF in this work was very similar to natural fibers previously studied, such as carnauba (107 °C) [ 52 ], caranan (64 °C) [ 66 ], PALF (75 °C) [ 72 ] and jute (61 °C) [ 73 ]. Although these events are slightly different from those approached by TG, they fall within the same temperature range.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…New concrete mixes and concepts are being developed across the world [41,42,44,[51][52][53][54] for meeting sustainable infrastructure demands or to attain novel properties, and few studies are reported for India as well [55][56][57]. This could even include fibre-reinforced concrete (both natural [58,59] and artificial: basalt nano-fibre [60]; steel fibre [56]), recycled aggregate concrete [61], and carbon nanotube reinforced concrete [62], among others. Fire and elevated temperature responses of these new materials, including thermal expansion, temperature profiles, deterioration, spalling, changes in strength and thermal properties with temperature, explosive spalling, post-event properties, etc., have been investigated internationally [63] but such data need to be carefully examined before such materials can be adopted for important infrastructure in India.…”
Section: Generation Of Fire/elevated Temperature Test Data For Indianmentioning
confidence: 99%
“…To accomplish such a goal, it is necessary that the manufacturers be provided with a plethora of environmentally friendly materials to choose from as substitutes for their current choices. Researchers have been actively working toward the production of green composites by experimenting with resins and fibers obtained from nature, and by making use of naturally derived materials (Väisänen et al, 2017;Peças et al, 2018;Souza et al, 2020;Vinod et al, 2020;Yorseng et al, 2020). They have attempted to replace the conventional materials used for the matrix and reinforcement.…”
Section: Introductionmentioning
confidence: 99%